The Moment Matrix of the Two-Stage Least-Squares Estimator of Coefficients in Different Equations of a Complete System of Simultaneous Equations - Nagar, A. L.; Gupta, Y. P. (Econometrica, 1970)
A. L. Nagar, Y. P. Gupta, The Moment Matrix of the Two-Stage Least-Squares Estimator of Coefficients in Different Equations of a Complete System of Simultaneous Equations, Econometrica, Vol. 38, No. 1 (Jan., 1970), pp. 39-49